Rendimiento académico en estudiantes universitarios con consumo de sustancias psicoactivas en Latinoamérica - Torres Suquilanda, Brandon Omar (2024)
During the university studies, young people are usually highly influenced by their environment and this, can lead to variations in their academic performance. That is why it is necessary for them to generate good study habits at an early stage that will enable them to enhance their learning quality, thus keeping them aloof from problems such as psychoactive substances consumption. When these psychotropic substances are introduced into the organism, they generate alterations within the cognitive-behavioural functions, which generate short- and long-term consequences, depending on the intensity and frequency of their use. The general objective of this paper was to describe the scientific evidence on the academic performance of university students who use psychoactive substances in Latin America. A descriptive literature review was conducted with a quantitative approach and a non-experimental design that included a total of 50 articles, from which 30 were excluded after finding duplicates, failure to meet inclusion criteria and irrelevance within the focus of the study. Consequently, we were able to analyse a total of 20 articles in Portuguese and Spanish which were no more than 18 years old, and contributed to the research aiming of cover more information. Statistical results have been found about Latin American students who consume psychoactive substances but hold a good academic performance. It was found that alcohol is the most frequent substance, which indicates the presence of more variables that can influence academic performance. It is concluded that there are multiple factors that can affect the student, one of them isinterpersonal relationships